Spiradenoma With Adenoid Cystic Carcinoma–Like Features. (June 2020) - Hopkins, Christina; Moyer, Amanda; Huttenbach, Yve Thaller
Abstract : Abstract: Spiradenoma is a benign cutaneous adnexal neoplasm that characteristically presents as a painful dermal nodule, often on the head or trunk. It has a distinct histologic phenotype and management involves surgical excision with low risk of recurrence. In comparison, adenoid cystic carcinoma (ACC) is a low-grade malignancy manifesting as an often painless subcutaneous mass with potential for local invasion, perineural extension, and high rates of recurrence after excision. We report the case of a 63-year-old male patient with a recurrent, painful hematoma-like cyst overlying the left lower extremity tibial tuberosity. A firm nodule was located at the base of the cyst, which was histologically consistent with spiradenoma. Interestingly, the lesion contained multifocal ACC-like components composed of epithelial basaloid cells surrounding pseudocystic structures filled with mucinous material. The ACC-like components did not demonstrate infiltration or perineural invasion. To the best of our knowledge, this is the second publication in the English literature regarding spiradenoma with an ACC-like pattern. Although a benign entity, knowledge of this morphological variant of spiradenoma is essential for diagnostic accuracy in these cases. If a limited biopsy captures only the ACC-like component of a spiradenoma, the lesion may be incorrectly diagnosed as ACC.